Oximetry of the brain - Vilkė, Alina; Macas, Andrius; Bieliauskaitė, Dalia; Bilskienė, Diana; Šuškevičienė, Ilona; Rugytė, Danguolė; Tamašauskas, Arimantas (Acta medica Lituanica, 2012)
Background. Devices allowing direct assessment of brain tissue oxygenation have showed promising results in clinical studies. However, estimation of brain oximetry still has some challenges. The aim of our study was to estimate the feasibility to monitor cerebral oximetry for neurosurgery patients in the Operating Room and in the Neurosurgery Intensive Care Unit, possible basic disturbances for the study and early results. Materials and methods. The prospective trial took place in a tertiary university setting – the Neurosurgery Department of the Lithuanian University of Health Sciences Hospital (Kaunas Clinics). The monitoring was performed with an INVOS® Cerebral / Somatic Oximeter, which is based on near-infrared spectroscopy. The monitoring places were the Operating Room, later the Neurosurgery Intensive Care Unit and for some patients the regular Neurosurgery Ward. All patients had acute open or closed traumatic brain injury and had undergone neurosurgery. Results. 52 patients were included in the study, while 36 operations were performed after traumatic brain injury with successful monitoring. Preoperatively GCS ranged from 3 to 15 (average 10.2 ± 4.6), all patients had no hypotension ranged from 214 mmHg to 112 mmHg (average 148.0 ± 26.6), the mean arterial pressure ranged from 155 mmHg to 61 mmHg (average 106.0 ± 21.8), only two patients had hypoxia with SpO2 of 86% and 76%, other values averaged 96.7% ± 4.3% . Hemoglobin preoperatively ranged from 162 g/l to 82 g/l (average 133.7 ± 17.9). The va lues of cerebral oxygenation preoperatively in the Operating Room were 42–96% (average 74.8 ± 10.8), and one patient with cerebral oxy genation of 15% bilaterally before surgery died in 24 hours after the surgery (normal values vary from 58 to 82%). The values varied from to 15–95% in the period of the operation. The biggest difference of cerebral oxygenation between brain hemispheres was registered as 42% and 68% before the intubation, 60% (±8.8) and 76% (±4.0) during the operation, 64% (±4.9) and 80% (±5.3) in the Intensive Care Unit. 13 patients died, 17 were discharged with GCS of 13–15 and 6 patients with GCS of 8–12. Conclusions. Monitoring of regional cerebral oximetry for neurosurgery patients can be performed, despite of its limitations: surgery or application of the Mayfield holder in the frontal region of the head, intra operative transcranial Doppler monitoring